Re-Desain Produk Wellhead untuk Menurunkan Cost dan Waktu Instalasi dengan Metode DFMA - khaliful ichsan; Ibnu Hafizh (Jurnal Teknik Mesin Unsyiah, 2021)
Design for Manufacturing and Assembly (DFMA) is a method used by designers and engineers to design a product with a reduce of components. The goal is to facilitate the manufacturing and assembly processes to reduce installation time, production and maintenance costs. This article discusses about the DFMA method to redesign conventional wellhead products into a wellhead compact spool (unihead) to make it easier and reduce the installation time and maintenance costs. DFMA analysis on wellhead product redesign showed a reduction in total install time from 188 hours to 30 hours. The effect of saving installation time the cost was also saved from $ 705,000 to $ 212,500 per well (well)